DOAC dipstick testing can reliably exclude the presence of clinically relevant DOAC concentrations in circulation: stroke, systemic or venous thromboembolism - Margetić, Sandra; Ćelap, Ivana; Huzjan, Arijana Lovrenčić; Puretić, Marijana Bosnar; Goreta, Sandra Šupraha; Glojnarić, Anesa Čajević; Brkljačić, Diana Delić; Mioč, Pavao; Harenberg, Job; Hetjens, Svetlana; Weiß, Christel (Thrombosis and haemostasis, 2022)
In certain clinical situations, it is necessary to determine whether clinically relevant plasma levels of direct oral anticoagulants (DOACs) are present. We examined whether qualitative testing of DOACs in urine samples can exclude DOAC plasma concentrations of ≥30 ng/mL. This prospective single-center cohort study included consecutive patients treated with an oral direct factor Xa inhibitor (DXI) (apixaban, n= 31, rivaroxaban, n = 53) and direct thrombin inhibitor (DTI) (dabigatran, n = 44). We aimed to define the negative predictive value (NPV) and other statistical parameters of detecting DXIs and DTIs by DOAC Dipstick at plasma concentrations of ≥30 ng/mL. We also determined the best-fit threshold plasma levels using chromogenic substrate assays by logistic regression analysis. Between July 2020 and July 2021, 128 eligible patients (mean age 66 years, 55 females) were included into the study. The NPVs and sensitivities for DXI and DTI of DOAC Dipstick were 100% at ≥30 ng/mL plasma, for specificities 6 and 21% and for positive predictive values 62 and 72%, respectively. All diagnostic statistical tests improved to values between 86 and 100% at best-fitting plasma thresholds of ≥14 ng/mL for DXI and ≥19 ng/mL for DTI. Visual analysis using the DOAC Dipstick was 100% in agreement with that of the optoelectronic DOASENSE Reader for all the three DOACs. DOAC Dipstick testing can reliably exclude the presence of DOACs in urine samples at best-fitting thresholds of >14 and >19 ng/mL in plasma. The performance of the DOAC Dipstick at detecting lower DOAC concentrations in plasma requires confirmation.